Conceptualization of Internet Meme in Media Communication Theory: A Review of Typologies - Natalya I. Klushina; Aida A. Syzdykova; Thi Thuy Dung Tran; Maria A. Vasilchenko (RUDN Journal of Studies in Literature and Journalism)
Explored the evolution of Internet memes as a polycode media phenomenon, from early web forms (1990s) to modern hybrid genres (2020s). Based on the corpus of viral memes from Russian and international platforms, their structural and meaningful transformations are analyzed in the context of the theory of memetics. The author identifies the key stages of meme culture development, demonstrating the relationship between the technological capabilities of platforms and genre diversity. The proposed typology integrates traditional formats (demotivators, macros) with innovative ones (mashups, AI-generated content), revealing the logic of their creation and distribution. The methodological framework combines discourse analysis, a linguosemiotic approach, and the study of platform constraints. The results reveal stable patterns of meme transformation under the influence of the digital environment, including the transition to short video formats and the growth of professional production, and demonstrate how meme semantics reflect a shift in generational values. Telegram’s role in professionalizing memes using its own creation tools has been reduced. The study contributes to the understanding of media virulence and cultural reflection in the digital age, emphasizing the role of memes as markers of sociocultural change.